"Mi voglio bene": a pediatrician-based randomized controlled trial for the prevention of obesity in Italian preschool children - Brambilla Paolo; Bedogni Giorgio; Buongiovanni Carmen; Brusoni Guido; Di Mauro Giuseppe; Di Pietro Mario; Giussani Marco; Gnecchi Manuel; Iughetti Lorenzo; Manzoni Paola; Sticco Maura; Bernasconi Sergio (BMC, 2010)
Abstract Background The first years of life are crucial to start preventive interventions that can have an impact on lifestyle and later overweight and obesity. Under the Italian National Health System (INHS), children are cared for by family pediatricians who perform health balances at regular intervals. The Italian Society of Preventive and Social Pediatrics (SIPPS) has designed a randomized controlled trial (RCT) to evaluate the effectiveness of family pediatricians for the prevention of childhood obesity in preschool children. We report the rationale and protocol of such trial, named the "Mi voglio bene" ("I love myself") study. Methods "Mi voglio bene" is a parallel-arm RCT. Family pediatricians willing to participate to the trial will be randomly assigned to a control group and to an experimental group. The control group will provide the usual standard of care while the experimental group will implement 10 preventive actions (promotion of breastfeeding, avoidance of solid foods, control of protein intake, avoidance of sugar-sweetened beverages, avoidance of bottle, active means of transportation, identification of early adiposity rebound, limitation of television viewing, promotion of movement, and teaching portion size) at 10 time points during a 6-yr follow-up. The main outcome measures is the prevalence of overweight and obesity at 6 years of age. The experimental intervention is expected to reduce the prevalence of overweight and obesity from 25% to 20% and the study requires a total of 3610 children. Each pediatrician will enroll 30 consecutive newborns into the study so that a total of 120 pediatricians will participate to the study. Discussion "Mi voglio bene" is expected to provide important information for the INHS and possibly other institutional child care settings about the effectiveness of a pediatrician-based approach to the prevention of childhood obesity. We published this study protocol with the aim of opening a discussion with all people interested in fighting childhood obesity and to receive useful criticisms.